Near Infrared Spectroscopy Measurements of Mitochondrial Capacity Using Partial Recovery Curves - Sumner, Maxwell D.; Beard, Samuel; Pryor, Elizabeth K.; Das, Indrajit; McCully, Kevin K. (Frontiers in Physiology, 2020)
Near-Infrared Spectroscopy (NIRS) has been used to measure muscle mitochondrial capacity (mVO2max) as the recovery rate constant of muscle metabolism after exercise. The current method requires as many as 50 short ischemic occlusions to generate 2 recovery rate constants. PURPOSE: To determine the validity and repeatability of using a 6-occlusion protocol versus one with 22 occlusions to measure muscle mitochondrial capacity. The order effect of performing multiple Mito6 test was also evaluated. METHOD: In two independent data sets (bicep n=7, forearm A n=23), recovery curves were analyzed independently using both the 6 and 22 occlusion methods. A third data set (forearm B n=16) was generated on the forearm muscles of healthy subjects using four 6-occlusion tests performed in succession. Recovery rate constants were generated using a MATLAB routine. RESULTS: When calculated from the same data set, the recovery rate constants were not significantly different between the 22 occlusion and 6 occlusion methods for the bicep (1.43+0.33min-1, 1.43+0.35min-1, p=0.81) and the forearm A (1.97+0.40min-1, 1.97+0.43min-1, p=0.90). Equivalence testing showed that the mean difference was not different than zero and the 90% confidence intervals were within 5% of the average rate constant. This was true for the Mito6 and the Mito5* approaches. Bland Altman analysis showed a slope of 0.21 min-1 and an r of 0.045 for the bicep dataset and a slope of -0.01 min-1 and an r of 0.045 for the forearm A dataset. When performing the four 6-occlusion tests; recovery rate constants showed no order effects (1.50±0.51 min-1, 1.42±0.54 min-1, 1.26±0.41 min-1, 1.29±0.47 min-1, P>0.05). CONCLUSIONS: The Mito6 analysis is a valid and repeatable approach to measure mitochondrial capacity. The Mito6 protocol used fewer ischemic occlusion periods and multiple tests could be performed in succession in less time, increasing the practicality of the NIRS mitochondrial capacity test. There were no order effects for the rate constants of four repeated 6-occlusion tests of mitochondrial capacity, supporting the use of multiple tests to improve accuracy.